Numerical Study on the Bending Resistance of Lightweight Built-Up Steel-Concrete Composite Beams - Andrea Rajić; Ivan Lukačević; Davor Skejić; Ivan Ćurković (Applied Sciences, 2023)
This paper investigates the bending resistance of an innovative lightweight composite floor system, LWT-FLOOR. The system consists of built-up cold-formed steel elements that are spot-welded and connected to the concrete slab using demountable shear connectors. As the system under investigation is new, the existing standards do not provide guidelines for calculating its bending resistance. This paper gives an overview of different analytical approaches and a comparison of calculated results using bending capacities from the numerical parametric study. Within the numerical parametric study, the influence of the height of the steel beam, the type and degree of shear connection, the connection between the steel elements, and the thickness of the corrugated web used for the bending capacity are investigated. Numerical results for the full shear connections resulted in lower bending capacities than the analytically calculated plastic bending resistances. However, numerically obtained bending capacities for partial shear connections were found to exceed the calculated characteristic non-linear bending resistances and bending resistances for partial shear connections. The obtained results will comprise the basis for further experimental tests, which will support the search for an optimal analytical approach for the bending resistance of the proposed composite system.